2009
DOI: 10.1038/onc.2009.137
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tumor suppressive function of P300/CBP-associated factor at frequently deleted region 3p24 in esophageal squamous cell carcinoma

Abstract: Deletion of 3p is one of the most frequent genetic alterations in many tumors, including esophageal squamous cell carcinoma (ESCC). In our recent study, deletion of 3p24 was frequently detected in ESCC and one candidate tumor suppressor gene (TSG), p300/CBP-associated factor (PCAF), was identified within the region. In this study, downregulation of PCAF was detected in 23/40 (57.5%) of primary ESCCs and 4/9 (44.4%) of the ESCC cell lines. A further study found that downregulation of PCAF was also associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…Despite the normal development of PCAF-null mice, 55 likely due to compensation by GCN5, PCAF is downregulated through methylation or allelic loss in a variety of cancers. 56,57 Notably, PCAF induces G 1 arrest and inhibits soft agar growth and tumorigenesis upon its reintroduction into cell lines established from these tumors. While the levels of several key cell cycle regulators, including p21, were evaluated in these studies, the mechanistic role of PCAF in this activity was not explored further.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the normal development of PCAF-null mice, 55 likely due to compensation by GCN5, PCAF is downregulated through methylation or allelic loss in a variety of cancers. 56,57 Notably, PCAF induces G 1 arrest and inhibits soft agar growth and tumorigenesis upon its reintroduction into cell lines established from these tumors. While the levels of several key cell cycle regulators, including p21, were evaluated in these studies, the mechanistic role of PCAF in this activity was not explored further.…”
Section: Discussionmentioning
confidence: 99%
“…21 These observations further demonstrated PCAF may function as a tumor suppressor gene and a possible connection between PCAF and p53-p21 Waf1/Cip1 pathway.…”
Section: Research Papermentioning
confidence: 93%
“…We recently showed that overexpression of Bcl-2 and like inhibitors in tumor cells can potentially be overcome by combining hGrzB and a BH3-mimetic agent such as ABT-737 and that the hGrzB death signal is remarkably long lived. 39 The well-described capacity of various human cancers to downregulate PCAF or ADA3 levels [40][41][42][43] would be expected to blunt combination therapies such as this, by repressing the latent pro-apoptotic signal provided by tBid.…”
mentioning
confidence: 99%
“…53 Finally, downregulation of PCAF has been observed in esophageal squamous cell carcinoma, ovarian and colorectal cancer. [40][41][42] Exactly how reduced expression and/or function of PCAF and ADA3 might lead to human diseases including cancer remains unclear. Small molecule inhibitors of PCAF have been reported; however, further studies on their specificity and role in disease are warranted 52,54 as is a further exploration of the potential impact of PCAF/ADA3 on immune-based cancer therapies.…”
mentioning
confidence: 99%